C0G dielectric ceramic material with high dielectric constant and high temperature stability as well as preparation method and application of C0G dielectric ceramic material
By using the combination of SrTiO3-CaTiO3 main powder and ZrO2-MgO-Bi2O3-MnO-SiO2-B2O3 formula powder, C0G ceramic materials with high dielectric constant and high temperature stability were prepared, and the dielectric constant of existing materials was solved. The problems of small and insufficient temperature stability meet the complex needs of high-frequency microwave technology.
Patent Information
- Application Number
- CN202411601036.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-11-11
AI Technical Summary
The existing C0G ceramic materials have a small dielectric constant and insufficient temperature stability, which cannot meet the complex demand for dielectric materials by high-frequency microwave technology, especially in the environment where the signal frequency is high and the temperature difference is large in millimeter wave technology, resulting in the communication system. Lifespan is affected.
SrTiO3-CaTiO3 is used as the main powder, and ZrO2-MgO-Bi2O3-MnO-SiO2-B2O3 is added as the formula powder. The dielectric constant is prepared by solid-phase synthesis, ball milling, granulation, glue removal and sintering. C0G dielectric ceramic material with a dielectric loss below 0.0001 and a temperature coefficient of -20~+20ppm/℃.
Ceramic materials with high dielectric constant and high temperature stability meet the high frequency and high reliability requirements of MLCC, reduce dielectric loss, improve the density and insulation performance of the material, and adapt to the functional density of complex electronic products. need.
Smart Images

Figure CN119241228A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of dielectric materials, and in particular to a C0G dielectric ceramic material with high dielectric constant and high temperature stability, and a preparation method and application thereof. Background Art
[0002] Multilayer ceramic capacitors (MLCCs) are composed of dielectric layers, staggered inner electrodes and outer terminal electrodes. They are an important type of passive components and have been widely used in almost all electronic fields. The latest trends of MLCCs are high capacitance, miniaturization, high-frequency applications, high reliability and low cost. In particular, with the rapid development of mobile communications and satellite communication systems, higher requirements have been put forward for the development of microwave frequency band MLCCs. With the development of millimeter wave technology, the application frequency band of RF MLCCs has gradually developed from hundreds of KHz to hundreds of MHz, and its use in military and civilian fields will become more and more prominent. C0G ceramic materials have the characteristics of low loss, good frequency and temperature stability, and good insulation performance. They are the key basic materials for achieving high reliability of RF MLCCs.
[0003] At present, the ceramic dielectric constant of C0G ceramic capacitors is relatively small, generally not exceeding 100. A higher dielectric constant can achieve a more certain capacitance value with a thinner dielectric layer to meet the increasing functional density requirements of complex electronic products in the current small volume context. Among the dielectric materials with a dielectric constant exceeding 100, some are based on the bismuth-based pyrochlore system. The pyrochlore material has high intrinsic dielectric loss and contains too much bismuth, which has the problem of element volatilization and alloying; some are ceramic materials based on the BaO-Ln2O3-TiO2 system (referred to as the BLT system) with a tungsten bronze structure, in which Ln2O3 is mainly La2O3, Sm2O3, and Nd2O3; and some are CaTiO3 and its modified ceramics and CaO-Li2O-Ln2O3-TiO2 and its modified ceramics. Although there are literature reports of dielectric constants as high as 245 and frequency temperature coefficients of 0.4CaTiO3–0.6 (Li 0.5 La 0.5 )TiO3 ceramics, but the dielectric temperature coefficient of this ceramic is relatively high, which can reach ±70ppm / ℃, which does not meet the C0G standard.
[0004] In the actual use environment of MLCC products, changes in capacity usually cause changes in the state of the electronic system in which it is located. For the rapidly developing millimeter wave technology, the signal frequency can be as high as tens of GHz, and a signal deviation of tens of ppm can cause changes in the overall operating frequency band of the system. A common example is that in the northwest of my country, due to the large temperature difference between day and night, there may be a 60°C temperature difference between day and night. The microwave dielectric ceramic material with a capacity-temperature characteristic of C0G index has a capacity-temperature characteristic range of up to 60ppm / °C within the operating temperature range, but this is not very adaptable to the current use environment, which will cause great challenges to the life of the communication system.
[0005] Therefore, it is meaningful to develop dielectric ceramic materials with better temperature stability by changing the material properties on the basis of improving the dielectric constant of C0G materials. Summary of the invention
[0006] In view of this, the purpose of the present invention is to propose a C0G dielectric ceramic material with high dielectric constant and high temperature stability and a preparation method and application thereof, so as to solve the problem of increasing the dielectric constant in high-frequency microwave dielectric ceramic materials while failing to further maintain or reduce the dielectric loss of the ceramic.
[0007] Based on the above purpose, the present invention provides a C0G dielectric ceramic material with high dielectric constant and high temperature stability, comprising the following raw materials in parts by mass: 100 parts by mass of a powder system, 0.5-3 parts by mass of a dispersant, 18-25 parts by mass of a solvent, and 20-25 parts by mass of a binder, wherein the powder system is prepared from 98 parts by mass of a main powder and 2 parts by mass of a formula powder system; the main powder comprises the following components in percentage by mass: 40-58% SrTiO3 powder and 40-58% CaTiO3 powder; the formula powder system comprises the following components in percentage by mass: 0.1-0.4% ZrO2 powder, 0.2-0.8% MgO powder, 0.2-0.6% Bi2O3 powder, 0.2-0.8% MnO powder, 0.2-0.4% SiO2 powder, and 0.05-0.15% B2O3 powder 。
[0008] The main powder is obtained by pre-sintering SrCO3, CaCO3 and TiO2 in a mass ratio of 1:1:2, the pre-sintering temperature is 1100-1200°C, and the pre-sintering time is 3-6h.
[0009] The dielectric constant temperature coefficient of the C0G type dielectric ceramic material is -20 to 20 ppm / °C.
[0010] The present invention also provides a method for preparing the COG dielectric ceramic material having high dielectric constant and high temperature stability, comprising the following steps:
[0011] S1. SrCO3, CaCO3 and TiO2 are taken in proportion, synthesized by solid phase method, and pre-sintered into SrTiO3 matrix and CaTiO3 matrix with average particle size of 200nm to 400nm, that is, main powder is obtained, wherein the pre-sintering temperature is 1100-1200℃, and the pre-sintering time is 3-6h;
[0012] S2, taking the main powder and the formula powder system according to the proportion, mixing them evenly, and obtaining a mixed material after ball milling and drying;
[0013] S3, mixing the mixed material with a binder, granulating to obtain a semi-finished product, and then tableting and debinding to obtain a ceramic green body;
[0014] S4. Sintering the ceramic green body to obtain a C0G dielectric ceramic material.
[0015] The ball milling in S2 is wet ball milling, the rotation speed of the ball milling is 40-60 r / min, and the time is 6h-24h.
[0016] The dispersant used in the wet ball milling includes polyethylene oxide resin, and the solvent includes ethanol, toluene and isopropanol; the grinding ball used is a 1mm zirconium ball. Among them, the dispersant is used to disperse the ceramic powder particles to prevent agglomeration. The dispersant of the present invention is for the purpose of achieving the aforementioned dispersion, and the dispersant can be polyethylene oxide resin and other resins. Based on the main powder + formula powder as 100 parts by mass, the amount of dispersant added is 0.5-3wt%. The solvent of the present invention includes but is not limited to ethanol, toluene and isopropanol. Based on the main powder + formula powder as 100 parts by mass, the amount of solvent added is 18-25wt%. Grinding is carried out using a ball mill.
[0017] The drying temperature in S2 is 90-200°C.
[0018] The binder in S3 is an alcohol solution of PVB, and the mass concentration of the binder is 20-25wt%. The invention has no special limitation on the source of the binder, and commercial products known to those skilled in the art can be used.
[0019] In the S3, the debinding temperature is 300-400° C., the time is 24-30 hours, and the debinding heating rate is 0.5-2° C. / min; thereby, the binder in the ceramic green body can be removed.
[0020] The sintering in S4 is carried out under a reducing atmosphere, the reducing atmosphere is H2-N2 with a volume fraction of 2%, the sintering temperature is 1200-1350°C, the time is 24-36h, and the sintering heating rate is 2-10°C / min. Sintering the ceramic green body under this sintering condition can make the capacitor ceramic body have good density, suitable core-shell structure and narrow particle size distribution, so as to meet the requirements of the prepared MLCC with excellent dielectric properties and capacitance-temperature characteristics.
[0021] The present invention also provides the application of the COG dielectric ceramic material with high dielectric constant and high temperature stability in multilayer ceramic capacitors.
[0022] Based on the C0G ceramic material with high dielectric constant and high temperature stability, a coating machine is used to coat it to obtain a ceramic film of corresponding thickness, and the corresponding inner electrode is printed on the ceramic film. Then, the ceramic capacitor green body is obtained through the staggered stacking design of the inner electrode and the ceramic film, and the corresponding ceramic capacitor MLCC is obtained through sintering into porcelain and copper plating of the outer electrode. Compared with ceramic capacitors prepared by existing materials, the MLCC prepared by this dielectric material not only meets the requirements of general C0G MLCC, but also has a relatively high dielectric constant and better temperature stability.
[0023] Beneficial effects of the present invention: The present invention designs a C0G ceramic powder with high dielectric constant and high temperature stability based on the main powder SrTiO3-CaTiO3 and the formula powder including the system of ZrO2-MgO-Bi2O3-MnO-SiO2-B2O3. After pre-sintering, ball milling, granulation, tableting, debinding, sintering and other steps, a C0G ceramic material with a dielectric constant of 110, a dielectric loss of less than 0.0001 and a temperature coefficient of -20 to +20ppm / ℃ is finally obtained.
[0024] Among them, SrTiO3 material has a higher dielectric constant, but has the problem of poor temperature stability. CaTiO3 material has good temperature stability, but its dielectric constant is small. By mutual doping of the two in a certain proportion, a main powder material with excellent dielectric constant and temperature stability is obtained. Zr ions partially replace Ti in the titanium oxide octahedron to play a pinning role, fill the vacancies in the crystal structure of the material, improve the order inside the material, increase the atomic stacking density, and ensure the stability of the capacity coefficient of the material within a wide temperature working range. Mg ions can inhibit excessive grain growth, improve the high-temperature insulation resistance of the material, and improve the dielectric temperature stability within the temperature range. Mn ions will prevent Ti from reoxidizing during the reoxidation stage. 4+ The reduction product Ti 3+The production of SiO2-B2O3 can effectively reduce the dielectric loss of ceramic powder and improve the insulation resistance. SiO2-B2O3 can effectively reduce the sintering temperature of ceramic powder, improve the density of the material, ensure that the grain size of the material is more uniform after sintering, and help reduce dielectric loss and improve the temperature stability of the material. 3+ Will Sr in SrTiO3 2+ Substitution leads to the relaxation of the lattice structure, which is beneficial to the Ti 4+ The movement of the dipoles increases the internal electric field, leading to an increase in the dielectric constant. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only for the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0026] Figure 1 FIG. 1 is a process flow chart for preparing C0G dielectric ceramic material according to the present invention. DETAILED DESCRIPTION
[0027] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.
[0028] It should be noted that, unless otherwise defined, the technical terms or scientific terms used in the present invention should be understood by people with ordinary skills in the field to which the present invention belongs. The words "include" or "comprise" and the like used in the present invention mean that the elements or objects appearing before the word include the elements or objects listed after the word and their equivalents, but do not exclude other elements or objects.
[0029] Example 1
[0030] like Figure 1 As shown, the method for preparing the COG dielectric ceramic material with high dielectric constant and high temperature stability in this embodiment includes the following steps:
[0031] 1. Take SrCO3, CaCO3 and TiO2 according to the proportion, synthesize them by solid phase method, and pre-sinter them into SrTiO3 matrix and CaTiO3 matrix with average particle size of 200nm to 400nm. The pre-sintering temperature is 1120℃ and the time is 3h.
[0032] 2. The main powder SrTiO3-CaTiO3 and the formula powder ZrO2-MgO-Bi2O3-MnO-SiO2-B2O3 system are mixed evenly in proportion (mixing 100 mass percent of calcined SrTiO3-CaTiO3 particles with an average particle size of 200nm to 400nm and the mass percentage of the formula powder, the composition of which is shown in Table 1), and then adding them into a ball mill for wet ball milling. The speed of the ball mill is 40r / min, and the ball milling time is 6h to obtain a uniformly mixed powder, wherein the dispersant is 2.5% by mass of polyethylene oxide resin, and the solvent is 20% by mass of toluene / ethanol mixed solvent. Then the powder is dried at a temperature of 150°C to obtain a mixed ceramic slurry.
[0033] 3. Add 25% by mass of PVB binder to the mixed ceramic slurry and granulate, press and debind. The debinding temperature is set to 350°C, the heating rate is 1°C / min, and the time is 24h, so as to remove the binder in the ceramic green body.
[0034] 4. The debinded ceramic green body was sent to a sintering furnace, wherein the sintering temperature was 1260°C, the heating rate was 3°C / min, and the sintering duration was 32 hours. The ceramic cooked body was subjected to the relevant evaluation tests described below, and the test results are listed in Table 1 below.
[0035] Example 2
[0036] The difference between this embodiment and embodiment 1 is that the mass percentage of each powder in the main powder and formula powder system is different. The composition and test results are shown in Table 1.
[0037] Example 3
[0038] The difference between this embodiment and embodiment 1 is that the mass percentage of each powder in the main powder and formula powder system is different. The composition and test results are shown in Table 1.
[0039] Example 4
[0040] The difference between this embodiment and embodiment 1 is that the mass percentage of each powder in the main powder and formula powder system is different. The composition and test results are shown in Table 1.
[0041] Example 5
[0042] The difference between this embodiment and embodiment 1 is that the mass percentage of each powder in the main powder and formula powder system is different. The composition and test results are shown in Table 1.
[0043] Example 6
[0044] The difference between this embodiment and embodiment 1 is that the mass percentage of each powder in the main powder and formula powder system is different. The composition and test results are shown in Table 1.
[0045] Example 7
[0046] The difference between this embodiment and embodiment 1 is that the mass percentage of each powder in the main powder and formula powder system is different. The composition and test results are shown in Table 1.
[0047] Example 8
[0048] The difference between this embodiment and embodiment 1 is that the mass percentage of each powder in the main powder and formula powder system is different. The composition and test results are shown in Table 1.
[0049] Comparative Example 1
[0050] The difference between this comparative example and Example 1 is that the mass percentages of the various powder materials in the main powder and formula powder system are different. The composition and test results thereof are shown in Table 1.
[0051] Comparative Example 2
[0052] The difference between this comparative example and Example 1 is that the mass percentages of the various powder materials in the main powder and formula powder system are different. The composition and test results thereof are shown in Table 1.
[0053] Table 1 Powder composition and test results of Examples 1-8 and Comparative Examples 1-2
[0054]
[0055]
[0056] It can be seen from Table 1 that the influence of SrTiO3-CaTiO3 main powder on the dielectric constant and temperature stability of ceramic materials is greater than that of the formula powder. The dielectric constant of the C0G dielectric ceramic material prepared by the present invention is between 101-121, and the dielectric loss is between 1.0-2.0×10 -4Within. From Examples 1-5, as the proportion of SrTiO3 material in the main powder increases, its dielectric constant increases, up to 121.0, but its TCC also increases, -22.4 ~ +21.6ppm / ℃. Example 3 When the proportion of SrTiO3-CaTiO3 is 49% each, a suitable dielectric constant and TCC will be obtained. Among them, the formula powder ZrO2-MgO-Bi2O3-MnO-SiO2-B2O3 has a certain influence on the performance system of ceramic powder. When the proportion of ZrO2 and Bi2O3 is 0.1% and 0.5%, the dielectric constant and TCC obtained are better. In Comparative Example 1, when the proportion of ZrO2 exceeds the required range and reaches 0.5%, its dielectric constant will become abnormally low, and the original intention of this design cannot be achieved. In Comparative Example 2, when the Bi2O3 ratio exceeds the required range and reaches 0.8%, although the dielectric constant is higher, the TCC condition becomes worse, which is -23.6 to +19.8 ppm / °C.
[0057] Those skilled in the art should understand that the discussion of any of the above embodiments is only exemplary and is not intended to imply that the scope of the present invention is limited to these examples; under the concept of the present invention, the technical features in the above embodiments or different embodiments can also be combined, the steps can be implemented in any order, and there are many other changes in different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity. Any omissions, modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A C0G dielectric ceramic material with high dielectric constant and high temperature stability, characterized in that: The invention comprises the following raw materials in parts by weight: 100 parts by weight of a powder system, 0.5-3 parts by weight of a dispersant, 18-25 parts by weight of a solvent, and 20-25 parts by weight of a binder. The powder system is prepared from 98 parts by weight of a main powder and 2 parts by weight of a formula powder system; the main powder comprises the following components in percentage by weight: 40-58% SrTiO3 powder and 40-58% CaTiO3 powder; the formula powder system comprises the following components in percentage by weight: 0.1-0.4% ZrO2 powder, 0.2-0.8% MgO powder, 0.2-0.6% Bi2O3 powder, 0.2-0.8% MnO powder, 0.2-0.4% SiO2 powder, and 0.05-0.15% B2O3 powder. 。 2. The COG dielectric ceramic material with high dielectric constant and high temperature stability according to claim 1, characterized in that: The main powder is obtained by pre-sintering SrCO3, CaCO3 and TiO2 in a mass ratio of 1:1:2, the pre-sintering temperature is 1100-1200°C, and the pre-sintering time is 3-6h.
3. The COG dielectric ceramic material with high dielectric constant and high temperature stability according to claim 1, characterized in that: The dielectric constant temperature coefficient of the C0G type dielectric ceramic material is -20 to 20 ppm / °C.
4. The method for preparing a COG dielectric ceramic material having a high dielectric constant and high temperature stability according to any one of claims 1 to 3, characterized in that: The steps include: S1. SrCO3, CaCO3 and TiO2 are taken in proportion, synthesized by solid phase method, and pre-sintered into SrTiO3 matrix and CaTiO3 matrix with average particle size of 200nm to 400nm, that is, main powder is obtained, wherein the pre-sintering temperature is 1100-1200°C, and the pre-sintering time is 3-6h; S2, taking the main powder and the formula powder system according to the proportion, mixing them evenly, and obtaining a mixed material after ball milling and drying; S3, mixing the mixed material with a binder, granulating to obtain a semi-finished product, and then tableting and debinding to obtain a ceramic green body; S4. Sintering the ceramic green body to obtain a C0G dielectric ceramic material.
5. The method for preparing a COG dielectric ceramic material having a high dielectric constant and high temperature stability according to claim 4, characterized in that: The ball milling in S2 is wet ball milling, the rotation speed of the ball milling is 40-60 r / min, and the time is 6h-24h.
6. The method for preparing a COG dielectric ceramic material having a high dielectric constant and high temperature stability according to claim 5, characterized in that: The dispersant used in the wet ball milling includes polyethylene oxide resin, the solvent includes ethanol, toluene and isopropanol; and the grinding balls used are 1 mm zirconium balls.
7. The method for preparing a COG dielectric ceramic material having a high dielectric constant and high temperature stability according to claim 4, characterized in that: The binder in S3 is an alcohol solution of PVB, and the mass concentration of the binder is 20-25wt%.
8. The method for preparing a COG dielectric ceramic material having a high dielectric constant and high temperature stability according to claim 4, characterized in that: In the S3, the binder removal temperature is 300-400°C, the time is 24-30h, and the binder removal heating rate is 0.5-2°C / min.
9. The method for preparing a COG dielectric ceramic material having a high dielectric constant and high temperature stability according to claim 4, characterized in that: The sintering in S4 is carried out under a reducing atmosphere, the reducing atmosphere is 2% by volume of H2-N2, the sintering temperature is 1200-1350°C, the time is 24-36h, and the sintering heating rate is 2-10°C / min.
10. Application of the COG dielectric ceramic material having high dielectric constant and high temperature stability according to any one of claims 1 to 3 in multilayer ceramic capacitors.
Citation Information
Patent Citations
Microwave tuned composite ceramic material and preparation method thereof
CN102219505A
Hyperstable-level fine ceramic material and preparation method thereof
CN104086173A
Temperature-stable X8R MLCC (multiplayer ceramic chip capacitor) medium material with low-temperature sintering effect
CN108083795A
Anti-reduction X8R type BaTiO3-based dielectric ceramic material and preparation method thereof
CN113277847A
High-performance anti-reduction barium titanate-based dielectric ceramic and preparation method thereof
CN113307622A
